Analisis Kesilapan Masalah·Masalah Berkaitan Nombor Perpuluhan dan Pecahan Bagi Pelajaran·Pelajaran Tahun Lima Sekolah Rendah - Md. Yunus, Aida Suraya (Penerbit Universiti Sains Malaysia, 1993)
One of the problems faced by many primary school students in mathematics is related to decimals and fractions. This paper discusses the findings of a study done on 151 Year Five students from six schools in Selangor, Negeri Sembilan and Melaka. In the study conducted, analysis were done on errors' in students' answers on a test formulated by the researchers.